Characterization of the properties of a selective, orally bioavailable autotaxin inhibitor in preclinical models of advanced stages of liver fibrosis. (17th January 2018) - Baader, Manuel; Bretschneider, Tom; Broermann, Andre; Rippmann, Joerg F; Stierstorfer, Birgit; Kuttruff, Christian A; Mark, Michael
Abstract : Background and Purpose: Autotaxin (ATX) is a secreted phospholipase which hydrolyses lysophosphatidylcholine to generate lysophosphatidic acid (LPA). The extracellular signalling molecule LPA exerts its biological actions through activation of six GPCRs expressed in various cell types including fibroblasts. Multiple preclinical studies using knockout animals, LPA receptor antagonists or ATX inhibitors have provided evidence for a potential role of the ATX/LPA axis in tissue fibrosis. Despite growing evidence for a correlation between ATX levels and the degree of fibrosis in chronic liver diseases, including viral hepatitis and hepatocellular carcinoma, the role of ATX in non‐alcoholic steatohepatitis (NASH) remains unclear. Experimental Approach: The relevance of ATX in the pathogenesis of liver fibrosis was investigated by oral administration of Ex_31, a selective ATX inhibitor, in a 10 week model of carbon tetrachloride‐induced liver injury and in a 14 week model of choline‐deficient amino acid‐defined diet‐induced liver injury in rats. Key Results: Oral administration of Ex_31, a selective ATX inhibitor, at 15 mg·kg −1 twice daily in therapeutic intervention mode resulted in efficient ATX inhibition and more than 95% reduction in plasma LPA levels in both studies. Treatment with Ex_31 had no effect on biomarkers of liver function, inflammation, or fibrosis and did not result in histological improvements in diseased animals. Conclusions and Implications: Our findings question the role of ATX in the pathogenesis of hepatic fibrosis and the potential of small molecule ATX inhibitors for the treatment of patients with NASH and advanced stages of liver fibrosis.